Developing power - McGuigan, M. (Human Kinetics, 2017)
Authored by the National Strength and Conditioning Association, Developing Power is the definitive resource for developing athletic power. With exercises and drills, assessments, analysis, and programming, this book will elevate power and performance in all sports.